STRUCTURAL APPROACH FOR IMPROVING TEACHERS EDUCATION STANDARD IN NIGERIA (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
In recent time,Nigeriahad witnessed unprecedented upsurge demand for education; the demand led to high students population explosion at different levels ofNigeriaeducational system.Nigeria, therefore being the giant ofAfricaneeds quality and standard education that will make the country ranked high among the development nations of the world. For this reason there is the need to restructure and reorganize teachers educational programme in order to cater for societal demands for education. This paper however examined the structural approach towards enhanced standard teachers education programme. It focused on the past and present structure of teachers education programme, the strength and weaknesses. The paper also makes structural approach recommendations to enableNigeriato be in the world class standard in teachers education programme and to achieve Nigerian educational goals. Implementation strategies was also suggested towards enhancing quality assurance and standard in Nigerian teachers education programme. It was finally concluded that effective structural approach should be accorded for Nigerian teachers education, in the interest of enhancing quality in teachers education programme inNigeria.